2015
DOI: 10.1128/iai.00042-15
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Play an Important Role in Protective Immunity against Coxiella burnetii Infection

Abstract: Coxiella burnetii is an obligate intracellular Gram-negative bacterium that causes the zoonotic disease Q fever. Although Q fever is mainly transmitted by aerosol infection, study of the immune responses in the lung following pulmonary C. burnetii infection is lacking. Neutrophils are considered the first immune cell to migrate into the lung and play an important role in host defense against aerosol infection with microbial pathogens. However, the role of neutrophils in the host defense against C. burnetii inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
1
18
1
Order By: Relevance
“…***, P Ͻ 0.001; ****, P Ͻ 0.0001. measured by quantitative real-time PCR. In addition, recent studies (13,14,25,(27)(28)(29)(30) demonstrated that both C. burnetii i.p. and respiratory infections cause similar systemic infections in mice and induce a significant and comparable splenomegaly at different time points postinfection.…”
Section: Figmentioning
confidence: 99%
“…***, P Ͻ 0.001; ****, P Ͻ 0.0001. measured by quantitative real-time PCR. In addition, recent studies (13,14,25,(27)(28)(29)(30) demonstrated that both C. burnetii i.p. and respiratory infections cause similar systemic infections in mice and induce a significant and comparable splenomegaly at different time points postinfection.…”
Section: Figmentioning
confidence: 99%
“…This finding suggests that ART has beneficial effects on the immune system beyond those measured with CD4 cell count. Neutrophils play a key part in the innate immune response to bacterial infection 11 . Known as the hallmark of inflammation, neutrophils are the first of the white blood cells to migrate towards a site of bacterial infection to begin killing the invading microbes 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Dendritic cells and monocytes may be the target cells of Orientia tsutsugamushi that can cause vasculitis and reticuloendothelial cell proliferation [37,38], which may be cause skin rash and lymphadenopathy. In contrast, C. burnetti can invade the monocytes and macrophages, leading to granuloma formation [39][40][41].Based on the above-mentioned ndings, we emphasize the meticulous physical examination to nd the characteristic presentation when a febrile patient comes.…”
Section: Discussionmentioning
confidence: 88%